The self-splicing intron in the Neurospora apocytochrome b gene contains a long reading frame in frame with the upstream exon. - Collins, R A (1988)
We have determined the DNA sequence of intron 1 and flanking exons in the mitochondrial apocytochrome b gene of the Neurospora laboratory strain 74A and the natural isolate North Africa. In contrast to a previous report, we find that this intron contains an open reading frame (ORF) of 951 bases in frame with the upstream exon. The putative intron-encoded protein resembles those of other intron ORFs with respect to length, calculated isoelectric point, and proportion of basic, acidic, polar, and non-polar amino acids; however, no amino acid sequences resembling the "decapeptides" characteristic of maturase-like ORFs were found. Coupled with the previous finding that this intron is capable of self-splicing in vitro in the absence of proteins, the observations discussed here raise the possibility that other introns with long, in-frame ORFs may also be capable of RNA-catalyzed splicing in vitro.